Analysis of the relationship between corporate social responsibility (CSR) spending and market stock price among Jordanian service firms - Mohammad Husam Odeh; Fadi Mohammed Alshannag; Bilal Eneizan; Abdelbaset M. Alkhawaldeh; Hebah Zaki Makhamreh (Cogent Business & Management, 2020)
In this study, the relationship of corporate social responsibility (CSR) spending and Market Stock Price was analyzed. The study sample comprised of 102 services firms listed on the Amman Stock Exchange (ASE) for the years 2010 to 2017. In particular, CSR spending reflects the actual CSR activities monetary contributions that are mandated to be disclosed in the firm's income statement. This study adopted the Generalized Method of Moment (GMM) to analyze the CSR spending-Market Stock Price relationship. The control variables included firm size, leverage and ownership. Based on the findings, no significant relationship exists between CSR spending and market stock price (MSP) in any direction. Added to this, control variables had no effect on MSP. However, the findings showed a significant positive effect of firm size on CSR spending and a negative effect of leverage on CSR spending, with no significant effect of ownership on the same. This study has several implications for the enhancement of the information and understanding of the firms' Market Stock Price as it shed light on the CSR spending-Market Stock Price relationship. Moreover, the study findings contribute to literature concerning CSR practices in the context of developing nations.
Keywords: 650; corporate social responsibility spending; market-based performance; market stock price; amman stock exchange